2021
DOI: 10.1186/s11556-021-00266-w
|View full text |Cite
|
Sign up to set email alerts
|

Sensor-based fall risk assessment in older adults with or without cognitive impairment: a systematic review

Abstract: Background Higher age and cognitive impairment are associated with a higher risk of falling. Wearable sensor technology may be useful in objectively assessing motor fall risk factors to improve physical exercise interventions for fall prevention. This systematic review aims at providing an updated overview of the current research on wearable sensors for fall risk assessment in older adults with or without cognitive impairment. Therefore, we addressed two specific research questions: 1) Can wear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 72 publications
1
33
0
5
Order By: Relevance
“…The findings from this study are consistent with prior research [54,55], suggesting the higher rate of falls by increasing age. Another important finding of this study points to the strong statistically significant association between richest individuals and fall as well as fall related injuries as compared to other individuals in lower wealth quintiles.…”
Section: Plos Onesupporting
confidence: 92%
“…The findings from this study are consistent with prior research [54,55], suggesting the higher rate of falls by increasing age. Another important finding of this study points to the strong statistically significant association between richest individuals and fall as well as fall related injuries as compared to other individuals in lower wealth quintiles.…”
Section: Plos Onesupporting
confidence: 92%
“…Accordingly, 18 systematic reviews were included in this umbrella review ( Figure 1 ). Nine of the reviews were developed in European countries [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], four in North American countries [ 26 , 27 , 28 , 29 ], three in Australia [ 30 , 31 , 32 ], one in Pakistan [ 33 ], and one in India [ 34 ]. The number of studies included in each review varied between 7 and 73, with an average of 32 studies, and a median of 25 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding training frequency, interventions consisting of three training sessions per week seem to be more effective than interventions with a lower training frequency which might not be able to achieve sufficient stimulus. Overall, none of the included studies used a sensor-based fall risk assessment, which has been shown to be feasible and able to successfully distinguish between groups of faller status ( Bezold, Krell-Roesch et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…E- and m-health technologies offer new opportunities for a more person-centered care that more effectively considers individual abilities and impairments ( Goh et al, 2017 ). Given the high heterogeneity of the NH population in terms of their cognitive and physical functioning, it is difficult to adjust conventional intervention programs (i.e., that are not based on e- or m-health) to individual needs ( Trautwein et al, 2020 ; Bezold, Trautwein et al, 2021 ; Barisch-Fritz et al, 2022a ). Furthermore, the interactive nature and implementation of game elements in digital applications can provide an enjoyable experience for elderly users ( Syed-Abdul et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%